A Computational Fluid Dynamics Simulation Model of Sediment Deposition in a Storage Reservoir Subject to Water Withdrawal - Mohammad, Mohammad E.; Al-Ansari, Nadhir; Knutsson, Sven; Laue, Jan (Water (Basel), 2020)
Siltation is one of the most common problems in storage projects and attached structures around the world, due to its effects on a project’s life span and operational efficiency. A three-dimensional computational fluid dynamics (CFD) model was applied to study the flow and sediment deposition in a multipurpose reservoir (Mosul Dam Reservoir, Iraq) subject to water withdrawal via a pumping station. A suitable control code was developed for the sediment simulation in intakes with multiblock option (SSIIM) model, in order to simulate a study case and achieve the study aims. The measured total deposited load in the reservoir after 25 years of operation and the measured sediment load concentration at different points near the pumping station intake were considered to validate the model results. The sediment load concentrations at several points near the water intake were compared; the percent bias (PBIAS) value was 3.6%, while the t-test value was 0.43, less than the tabulated value, indicating fair model performance. The model sensitivity to grid size and time steps was also tested. Four selected bed level sections along the reservoir were compared with the simulated values and indicate good performance of the model in predicting the sediment load deposition. The PBIAS ranged between 4.8% and 80.7%, and the paired t-test values indicate good model performance for most of the sections.